Perceptual Alignment: Investigating EFL Teachers' Perspectives on Students' Writing Difficulties - Amalia, Novika (General English Education, 2025)
The study investigates the alignment between EFL teachers' perceptions of students' writing difficulties and the actual performance of students in vocabulary, grammar, organization, and mechanics. Using semi-structured interviews with five certified EFL teachers and written tests from 28 junior high school students, the research employs thematic and content analysis. Results show strong alignment in vocabulary and grammar, highlighting issues such as limited vocabulary range and frequent grammatical errors. However, significant misalignment is found in organization and mechanics, with teachers overestimating students' skills in structuring essays and using punctuation. The findings underscore the pressing need to address these gaps, as the misalignment between teacher perceptions and student performance hinders effective instruction and student progress in writing proficiency. Bridging this gap is crucial for fostering holistic EFL writing skills. Suggestions include structured feedback rubrics, peer evaluations, and professional development workshops to enhance teaching practices. This study contributes to improving EFL instruction by identifying gaps in teacher-student alignment and proposing targeted interventions for better writing proficiency.